Sexual Abuse against Female Gender: Four-years Report of Three Reception Centers in Dakar - K. Niang; A. Gueye; P. Ndiaye (Research Developments in Medicine and Medical Science Vol. 2, 2023)
Establishing the epidemiological profile of sexual abuse was the goal of this investigation. Sexual abuse is a public health problem because of its magnitude, its severity on the victims and their vulnerability linked to human behavior. The study had two parts and spanned four years (2009–2012). One, quantitative, was based on the use of all victim records from three reception centers. The other, qualitative, focused on interviews of professionals involved in the care of victims. There were 78 cases in total. The victims, with 14(±7) years on average age, were mostly educated in French (72%), from Dakar area (85%), students (61%), under parental supervision (55.1%), and less than 4 siblings (59%). The alleged perpetrators, whose average age is 29 (±11) years, were predominantly acquaintances (51%), parents (36%) for the victims, and of unspecified profession (69.23%). The sexual abuse, incestuous in 18% of cases, was more frequently linked to rape (68%) committed at the alleged perpetrators’ (37.2%) and followed by behavioural disorder (47%), pregnancy (15%), alcoholism and/or running away (12%). According to professionals, the victims are typically minors from disadvantaged areas. The victim’s post-traumatic treatment is delayed as a result of the victim’s judicial concern, which is often the first reaction of parents. The management should focus on socio-economic development; Information, education and communication, favour prevention and accessibility of functional structures with competent and motivated professionals, facilitate the treatment of residual cases.